2019
DOI: 10.1038/s41409-019-0520-6
|View full text |Cite|
|
Sign up to set email alerts
|

High-resolution HLA phased haplotype frequencies to predict the success of unrelated donor searches and clinical outcome following hematopoietic stem cell transplantation

Abstract: HLA matching is a critical factor for successful allogeneic hematopoietic stem cell transplantation. For unrelated donor searches, matching is usually based on high-resolution typing at five HLA loci, looking for a 10/10 match. Some studies have proposed that further matching at the haplotype level could be beneficial for clinical outcome. In this study, we determined the phased haplotypes of 291 patients using family members and segregation analysis. The sum of ranks of the haplotypes carried by patients was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 45 publications
3
15
0
Order By: Relevance
“…Recently, it has been shown that both high-resolution HLA typing and haplotyping are important in hematopoietic stem cell transplantation for both unrelated and related donors in reducing post-transplantation adverse outcomes (Agarwal et al, 2017;Buhler et al, 2019); a single high-resolution HLA mismatch may lead to a similar negative effect on outcomes as a low-resolution one (Fuji et al, 2015;Armstrong et al, 2017). Therefore, it has been suggested that highresolution HLA typing can reduce the likelihood of missing a clinically significant mismatch compared to traditional lowresolution typing, especially in developing countries where highresolution HLA typing methods are not widely available (Agarwal et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that both high-resolution HLA typing and haplotyping are important in hematopoietic stem cell transplantation for both unrelated and related donors in reducing post-transplantation adverse outcomes (Agarwal et al, 2017;Buhler et al, 2019); a single high-resolution HLA mismatch may lead to a similar negative effect on outcomes as a low-resolution one (Fuji et al, 2015;Armstrong et al, 2017). Therefore, it has been suggested that highresolution HLA typing can reduce the likelihood of missing a clinically significant mismatch compared to traditional lowresolution typing, especially in developing countries where highresolution HLA typing methods are not widely available (Agarwal et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Matching probability analyses using population-specific HLA haplotype frequencies allow targeted planning of donor center recruitment strategies (40). Beyond that, a positive impact on outcome of HSCT is proposed for the additional matching of non-HLA genes located in the MHC region via haplotype matching between patient and donor, but study results are still inconclusive (41)(42)(43).…”
Section: Introductionmentioning
confidence: 99%
“…The overall outcome is also dependent on patient age and disease status at the time of transplantation. Despite the advances, such as accurate allelic matching, treatment regimens, and improved supportive care treatment, it still holds true that HSCT shows superior outcomes with fewer complications and higher survival rate when a matched sibling donor is available [24,26,27].…”
Section: Pgt With Human Leucocyte Antigen (Hla) Matching: Clinical Utmentioning
confidence: 99%